Factors related to health literacy for prevention of dengue hemorrhagic fever of school age children in Nadee District, Prachin Buri Province - Chayyaphong, Adun; Onmasen, Parimon (Disease Control Journal, 2020)
This study is a descriptive study research. The research aimed to investigate the re-lationship between self-efficacy, social supporting information about dengue hemorrhagic fever and health literacy. The study subjects were 320 school-age children in Nadee district, Prachin Buri province. All data were collected using questionnaires. These descriptive data were analyzed by descriptive statistics. Analysis of the relationship was carried out by Pearson’s correlation coefficient test. Results revealed that most of the samples were fe-male at 56.2 percent and the average age was 11.0 years old. The majority of them were found to have an inadequate level of health literacy at 53.8 percent, and limited level of literacy at 33.1 percent. Moreover, a correlation study revealed that self-efficacy and social supporting information about dengue hemorrhagic fever were significantly associated with health literacy (r= 0.269, p< 0.001 and r= 0.420, p<0.001, respectively) A learning process for the development of health literacy for the purposes of preventing dengue hemorrhagic fever among school-age children should take into consideration self-efficacy and support-ing information.